Construindo pontes: o ingresso de estudantes indígenas na UFSCar: uma discussão sobre "cultura" e "conhecimento tradicional" - Bó, Talita Lazarin Dal' (2010)
The presence of indigenous students at the universities has been potencialized by programs of inclusion and increased expressively, demonstrating the crescent interest of these populations by the scholar education and by the continuity of their studies. This presence has been raised several questions at the Universities, at the most general society, at the State, at the academy, and by part of indigenous population that discuss the theme of the public policies of inclusion and the theme of the knowledge and the teaching process and the differentiated learning. This dissertation presents the process of inclusion of indigenous students at the Federal University of São Carlos, analyzing the formulation and the implantation of the proposal of affirmative actions in this university and, over all, from the indigenous students experiences that entered into it in 2008 and the questions that they had presented. For this, it proposes a reflection about themes like interculturaly , traditional knowledge and culture , already present a long time ago at the discussion about specific indigenous scholar education and, recently, potencialized in the debate about the ingression of indigenous at the college. It tried to demonstrate how much of the debate is present (or not) in the experiences of these indigenous students and how they answer to these process, building their own ways and showing us the possible bridges of connection.